P0088THE INFILTRATION OF T AND B LYMPHOCYTES AND NK CELLS IN KIDNEY BIOPSIES OF PATIENTS WITH FABRY DISESE UNDER ENZYME REPLACEMENT THERAPHY. (6th June 2020) - Turkmen, Kultigin; Esen, Hasan; Karaselek, Mehmet Ali; Celikbilek Celik, Seyma; Baloglu, Ismail; Guner, Sukru; Reisli, Ismail; Keles, Sevgi
Abstract: Background and Aims: Fabry Disease (FD) is a lysosomal glycosphingolipid storage disorder. Kidneys are affected in FD. Despite enzyme replacement theraphy (ERT), some patient still have an ongoing deterioration of renal functions probably secondary to inappropriate immune responses. There is no data regarding NK cell subtypes and the exact relation with B-T lymphocytes and NK cells in patients with FD. We aimed to analyze subtypes of NK cells in patients with FD and compared these results with healthy subjects. Additionally, we analyzed the renal biopsy (RBx) materials of our patients prior to ERT in terms of B, T and NK cell infiltration and compared these cells in some of our FD patients after 4 years of ERT. Method: 15 patients with FD and 10 healthy controls were included in the study. Of 15 patients, 8 patients were receiving agalsidase alfa or beta. Blood samples obtained from both group were taken into 2 ml EDTA tube to evaluate peripheral NK cell subgroups according to CD56 and CD16 expression and CD3, CD4, CD8 expression to determine subtypes T cells. These cells were evaluated by flow cytometry technique. The RBx of 10 patients with FD were evaluated before ERT and 3 were reevaluated after 4 years of ERT in terms of T-B, NK and plasma cells infiltration of kidney. The paraffin blocks of specimens were examined with HE, PAS, Masson-trichrome and toluidine blue staining and frozen blocks were examined with red-oil 10 staining Results: The characteristics of patients with FD and healthy controls are depicted in Figure 1. Except proteinuria, there were no significant differences in terms of biochemical parameters between two groups. According to flow-cytometric analyses, total percentage of NK and T helper 1, 2, 17 and Treg cells of FD patients are similar to controls (Fig 1). When we analyzed subgroups of NK cells and determined that CD56 dim CD16 dim NK cells were increased, however, CD56 dim CD16 bright NK cells were decreased in patients with FD compared to controls (Fig1). We performed RBx of 10 patients. The percentages of CD3, 4, 8 positive Tcells, CD19, CD20 positive B cells, CD 16, 56 positive NK cells and CD 138 positive plasma cell infiltration are shown in Fig 2. According to RBx findings prior to ERT, all patients had interstistial fibrosis (IF), podocyte vacuoles (PV), podocyte inclusion (PI), CD3, CD4, CD16, CD56 positivity at different levels. In contrast, almost none of the patients had CD19, CD20, CD138 positivity. We rebiopsied 3 patients after 4 years of ERT and reevaluated specimens in terms of IF, global and segmental sclerosis (SS), PV, PI and the percentages of CD3, CD4, CD16, CD56, CD 19, CD 20, CD 138 positivity. 2 rebiopsied patients from the same family had increased serum creatinine and proteinuria despite 4 years of regular ERT. In the second biopsy of these two patients, we found that global sclerosis (GS), IF and PI are increased and abundant CD19, CD20 and CD 138 positive cells were seen which were almost absent in the first biopsy. The other patient from another family, had mildly increased proteinuria and had no creatinine increment after 4 years of ERT. In this patient, we found that GS, SS, IF, PI and arterial sclerosis were increased, however CD 3, 4, 8 positive T cells were decreased and no changes in the percentage of CD16, 56 positive NK cells. We could not demonstrate CD 19, 20, 138 positivity in the latter patient. Conclusion: Our group, for the first time, demonstrated that CD56 dim CD16 dim subtype of NK cells is increased in FD which is closely associated with cellular cytotoxity in normal population. Additionaly, CD 19 and CD 20 positive B cell infiltration are increased and glomerular and interstitial changes are advanced in some patients with ongoing kidney function deterioration despite 4 years of regular ERT. Hence, infiltration of Bcells in the kidneys of patients under ERT might change our therapeutic approaches in the near future. Further studies are needed to clarify the exact roles of B T and NK cells in FD.